[Book review] Jan Rüdiger, All the King’s Women. Polygyny and Politics in Europe, 900–1250 - Hermanson, Lars (Journal of Northern Studies, 2024)
Review of: Jan Rüdiger, All the King’s Women. Polygyny and Politics in Europe, 900–1250 (The Northern world 88), Leiden: Brill 2020